Culturally adapted cognitive behavioural group therapy for mental disorders in refugees plus problem solving training (ReTreat): study protocol for a multicentre randomised controlled trial. Issue 11 (11th November 2022) - Kananian, Schahryar; Kip, Ahlke; Schumm, Hannah; Giesebrecht, Julia; Nicolai, Anica; Schade-Brittinger, Carmen; Reese, Jens-Peter; Weise, Cornelia; Mewes, Ricarda; Morina, Nexhmedin; Ehring, Thomas; Stangier, Ulrich
Abstract : Introduction: Since a high proportion of refugees in Germany suffer from mental disorders, culturally adapted treatments are needed that target a broad range of symptoms. There is much evidence for the efficacy of culturally adapted cognitive behavioural therapy (CA-CBT). Given the promising results of CA-CBT, the combination with problem solving training (CA-CBT+) represents a novel approach that potentially improves the refugees' ability to cope actively with psychosocial problems. This randomised controlled trial evaluates the efficacy of 12-session outpatient CA-CBT+ compared with to treatment as usual (TAU) in a sample of refugees suffering from at least one DSM-5 disorder. Methods and analysis: The present study will be carried out as two-group randomised trial with 1:1 individual allocation to either (1) culturally adapted cognitive behavioural therapy in a group setting (CA-CBT+) or (2) TAU. The study takes place at four sites in Germany, randomising in total 138 adult refugees with at least one primary DSM-5 diagnosis to the treatment conditions. In CA-CBT+ the patients receive 12 sessions of 120 min duration over the course of 12 weeks providing psychoeducation, meditation and other techniques of emotional regulation, stretching and problem solving training. The primary outcome is treatment response operationalised by a clinically significant change in General Health Questionnaire (GHQ-28) score. Follow-up visits will take place 3 and 9 months after the end of the intervention. Secondary outcomes include changes in psychopathological symptoms, somatic symptoms and quality of life. Intention-to-treat analysis will be performed. Adverse and serious adverse events will be analysed. Further, healthcare usage and economic outcomes will be assessed and analysed. Primary and secondary outcomes will be analysed using appropriate statistical methods. Ethics and dissemination: The study has been approved by the Ethics Commission of the German Psychological Society (ref: StangierUlrich2019-1018VA). Results will be disseminated via presentations, publication in international journals, and national outlets for clinicians. Furthermore, intervention materials will be available, and the existing network will be used to disseminate and implement the interventions into routine healthcare. Trial registration number: DRKS00021536.